Contextualising the Impact of COVID-19 Pandemic on Attitudes of People to Follow SOPs: Study of Smart Lockdown across Generation X, Y and Z in Pakistan - Alvi, Mobashira; Ehsan, Nadeem (Pakistan Journal of Humanities and Social Sciences, 2023)
Pandemics such as the Black Death and cholera in the past sowed doubt among the human population and triggered widespread fear and panic. When it comes to the COVID-19 pandemic, people all around the world seem to have the same reactions. This study aimed to determine if and to what extent people's compliance with SOPs affects the rate at which the disease spreads. This study uses the theoretical underpinnings laid out by the Theory of Planned Behavior (TPB) and the Protection Motivation Theory (PMT) to inquire about people's awareness, understanding, and perspectives. Intentions toward COVID-19 SOPs were investigated by digging into these independent factors. Voluntary and non-voluntary control behaviour intents can be predicted by the independent variables. The research is conducted in two phases and used a combination of methods, i.e., quantitative and qualitative. The findings from Stage I's demographic exploration has been put to the test in Stage II's empirical analysis. Also, the results were compared over three generations (X, Y, and Z) to examine generational differences and determine whether or not adjusting to how individuals of different ages see pandemics will help reduce their societal impact. Among the three selected generations, Gen Z was the most influenced by information and advice campaigns to build a perception of danger that has shaped their protective behaviour, as evidenced by the results of the qualitative study's 42 face-to-face interviews. Yet, Gen Y and Z were more influenced by informal standards. In stage II, the questionnaire (n=510) was used to conduct empirical testing of the topics identified in qualitative thematic analysis, and the results indicated that risk perception was a significant predictor of protective behaviour. No substantial moderating influence of risk perception on knowledge and protective behaviour was found, according to mediation and moderation analysis.